2013
DOI: 10.1179/2047773213y.0000000096
|View full text |Cite
|
Sign up to set email alerts
|

Clinical spectrum and treatment outcome of severe malaria caused byPlasmodium vivaxin 18 children from northern India

Abstract: Objective: The study was intended to document the clinical profile and treatment outcome of severe malaria caused by Plasmodium vivax (P.vivax) in children hospitalized in a tertiary care centre of northern India. Methods: This prospective observational study was performed among children admitted with severe malaria at a tertiary care referral hospital of northern India from January 2012 to December 2012. Information was recorded pertaining to clinical symptoms at presentation, examination findings, biochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 10 publications
3
14
1
Order By: Relevance
“…Some studies failed to address the assessment of ‘common outcomes’ [10], [28], [30], [35], [37], [41], [42], [44], [45]. Failure to address any of these important criteria could affect the validity of their study process and/or outcome measurements.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies failed to address the assessment of ‘common outcomes’ [10], [28], [30], [35], [37], [41], [42], [44], [45]. Failure to address any of these important criteria could affect the validity of their study process and/or outcome measurements.…”
Section: Resultsmentioning
confidence: 99%
“…In present study we found that children having malaria presented with fever (24, 100%) 18 The stool examination showed the frequency of parasitic infection was Amoeba 1 (7.1%), Giardia 1 (7.1%), Ascariasis 6 (42%), and Hookworms 6 (42%) in total of 14 cases. Bechir et al in their study found that prevalence of intestinal parasitic infection was 75% (CI 68-83) among women and 60% (CI 53-66) among children.…”
mentioning
confidence: 45%
“…But no research could be found to establish relation between artseunate therapy and malaria-induced bleeding. 13 So this observation needs further validation.…”
Section: Outcomementioning
confidence: 95%
“…13 In another study by Desai PD et al, 90% patients with cerebral malaria recovered after getting injectable Artesunate.…”
Section: Outcomementioning
confidence: 95%
See 1 more Smart Citation